A sociology of institutionalisation of the 'mentally ill' in Ireland - Brennan, Damien John (Trinity College (Dublin, Ireland). Department of Sociology, 2007)
A Sociology of Institutionalisation of the ‘Mentally ill’ in Ireland. This dissertation proposes that the trajectory of the institutionalisation of ‘mentally ill’ persons in Ireland can be understood as a multi-layered social process resulting from an interconnectivity of various social forces and human actions, rather than any biological or psychological phenomenon that is situated within the mental state of those institutionalised. A national public asylum system was established during the early nineteenth century, which developed into a significant physical and social feature of Irish communities. This system entailed the building of a network of asylum buildings, the establishing of an administrative bureaucracy and the development of institutional policy and routine, all of which were controlled centrally through the colonial administrative centre at Dublin Castle. These asylum buildings were added to and expanded throughout the mid to late nineteenth century and, along with other institutions such as workhouses, private asylums and gaols, they provided accommodation for individuals who were constructed as being ‘mentally ill’. The utilisation of these institutions continued uninterrupted post partition in 1922, their eventual closure and sale being officially endorsed in national social policy in 2006. This dissertation draws from historical sociology, particularly interpretative and critical methodologies, to guide an analysis of the social forces that have underpinned the trajectory of these institutions on the island of Ireland from 1800-1922 and the Republic of Ireland thereafter. A central feature of this study is the identification of long term trends in institutional residency across this time span. This is achieved though the development of a detailed empirical data set that is based on an analysis of original copies of each report of the Inspector of Asylums in Ireland, later the Inspector for Mental Hospitals, for each year from 1846 to 2000, along with other parliamentary papers, special reports and archival material. This data is presented through the use of scatter plot graphs and tables that illustrate the gross level of residency and rates per 100,000, along with the level and gender of residency within each institution type. The comparative international context is also examined along with several axes of stratification including urban / rural divides and social class. This analysis reveals an overall trajectory of institutional residency that commenced in the early nineteenth century, a period of significant growth between 1830 and 1890, increased utilisation up to a high point in 1956, and a steady decline from that time to the present. It is also demonstrated that the actual rate of institutional utilisation in Ireland is particularly high by international standards. This empirical information provides a foundation on which the various social forces pertinent to the trajectory of institutional usage can be considered. This is presented in two sections, the first addresses the foundation and expansion of these institutions, the second their demise and eventual closure. Core features that are identified as being important include: the political context, governance and social policy; the relationship between church and state; changing economic structures and social deprivation; professionalisation; legalisation and systems of admission and discharge; categorisation and diagnostic criteria; international developments; and family dynamics. Based on this analysis it is proposed that Irish institutionalisation of the ‘mentally ilf resulted from the interaction of these social forces along with human action of individuals, families and communities. A core sociological understanding that emerges is the impact of particular conjunctures of social forces that have punctuated the major points of change within the trajectory of institutional usage.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin